2013
DOI: 10.5603/cj.2013.0076
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of cardiac resynchronization therapy on arterial distensibility and serum norepinephrine levels in advanced heart failure

Abstract: Background: Cardiac resynchronization therapy (CRT) has become an accepted method for treating refractory heart failure (HF). (Cardiol J 2013; 20, 3: 304-309)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…An increasing number of experimental studies have suggested that PVN is key in the progression of HF (26). Studies have found that CRH and NE contribute to sympathoexcitation in rats with ischemia-induced HF (32,33). The results of the present study are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…An increasing number of experimental studies have suggested that PVN is key in the progression of HF (26). Studies have found that CRH and NE contribute to sympathoexcitation in rats with ischemia-induced HF (32,33). The results of the present study are consistent with these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…Because NE can bind various types of adrenergic receptors on the surface of immune cell membranes and then can induce intracellular signal transduction (upregulate the cAMP expression) when the serum NE level has risen. 50 Hence, BDE-209 enhanced serum NE levels and attenuated the content of NE in the hypothalamus by maternal transmission, generating the restraint of female offspring's sympathetic nervous system functions. In addition, the CNS will restrain the endings of the parasympathetic nerve from releasing Ach and impairing the bind with α7nAchR on the immune cell membrane when it receives the immune stimulation signal from the body by inhibiting the release of proinflammatory factors from immune cells through intracellular signaling pathway, the inflammatory response of the body is inhibited.…”
Section: Discussionmentioning
confidence: 99%